(untitled) (Global Scientific Review, 2025)
Today, youth infantilism is a pressing problem that significantly impacts societal development. The low ability of young people to make independent decisions and actively participate in social and economic life limits their adaptability to life and negatively affects their level of preparation for the future labor market. This article analyzes the main forms of youth infantilism, including the concepts of social, psychological, and economic infantilism. The article provides practical recommendations for reducing the level of youth infantilism and increasing their adaptability to society. In particular, it proposes comprehensive approaches to teaching young people to independently choose their life path, creating the necessary conditions for them to achieve economic and professional independence, and increasing the social activity of young people